2018
DOI: 10.1101/474072
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RADAR: annotation and prioritization of variants in the post-transcriptional regulome of RNA-binding proteins

Abstract: RNA-binding proteins (RBPs) play key roles in post-transcriptional regulation and disease. Their binding sites cover more of the genome than coding exons; nevertheless, most noncoding variant-prioritization methods only focus on transcriptional regulation. Here, we integrate the portfolio of ENCODE-RBP experiments to develop RADAR, a variant-scoring framework. RADAR uses conservation, RNA structure, network centrality, and motifs to provide an overall impact score. Then it further incorporates tissuespecific i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Disease-causal variant mapping is one of the most important applications of distal regulatory element mapping. Lines of evidence have demonstrated that accurate and compact annotations can significantly increase the statistical power for both somatic and germline variant mapping in disease studies (Fu et al ., 2014; Zhang, Liu, et al ., 2020; Zhang, Lee, et al ., 2020). Therefore, we further tested whether our condensed enhancer definitions can benefit variant prioritization and interpretations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Disease-causal variant mapping is one of the most important applications of distal regulatory element mapping. Lines of evidence have demonstrated that accurate and compact annotations can significantly increase the statistical power for both somatic and germline variant mapping in disease studies (Fu et al ., 2014; Zhang, Liu, et al ., 2020; Zhang, Lee, et al ., 2020). Therefore, we further tested whether our condensed enhancer definitions can benefit variant prioritization and interpretations.…”
Section: Resultsmentioning
confidence: 99%
“…We further evaluated the quality of our compact enhancer annotation from DECODE via the enrichment of rare variants with a simple but validated assumption -key functional regions in the genome are under strong negative selection and hence are depleted in common variants (Fu et al, 2014;Zhang, Liu, et al, 2020). Therefore, we compared the rare variant enrichment in the refined and original positive enhancer regions.…”
Section: Decode's Compact Enhancer Predictions Are Highly Conserved Amentioning
confidence: 99%
“…We further evaluated the quality of our compact enhancer annotation from DECODE via the enrichment of rare variants with a simple but validated assumption—key functional regions in the genome are under strong negative selection and hence are depleted in common variants ( Fu et al, 2014 ; Zhang et al, 2020b ). Therefore, we compared the rare variant enrichment in the refined and original positive enhancer regions (and against ENCODE NPC cCREs, FANTOM human enhancers, FANTOM neuronal stem cell enhancers in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We have made this RNA variant annotation and prioritization tool available as an open-source software at https://github.com/gersteinlab/RADAR [46]. The source code is released under MIT License.…”
Section: Supplementary Informationmentioning
confidence: 99%